THE ROLE OF E-COMMERCE IN CREATING CREATIVE AND INNOVATIVE MSME MANAGERS THROUGH TRAINING - Baby Poernomo; Avradya Mayagita (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Empowering MSMEs is one of the national priorities considering their great potential and greatness in facing the economic crisis, helping to absorb labor, and as a motor of national economic growth. Therefore, MSMEs need to be managed by leaders who are creative and agile in all changes. This study aims to answer the question of how to implement "creative thinking and Innovation" training for MSME owners and managers and what problems are faced in implementing the training and what solutions are offered to overcome existing problems. This is a qualitative study with a phenomenological approach. Data collection was obtained through semi-structured interviews with MSME managers and training managers. The results of the study indicate that the role of E-commerce is very large in providing creative thinking training for MSME managers. To maintain the quality of training, aspects of materials, methods and instructors must be the concern of the organizers.